Evaluation of the use of microemulsions based on Moringa Oleifera Lam oil saponified as continuous phase of drilling fluids: Analysis of rheological properties (Research, Society and Development, 2021)
In oil exploration, one of the main activities is the drilling of wells, in which it is necessary to use the so-called drilling fluids. Due to its great importance, it has been sought to develop drilling fluids with improved properties and, to that end, studies show that microemulsified systems can be viable for this application, since they are more stable than emulsified systems, which makes them more efficient. The objective of this work was the development of a drilling fluid using as its continuous phase microemulsioned systems based on Moringa Oleifera Lam saponified oil. In the development of the microemulsioned system were used distilled water (aqueous phase), moringa oil (oily phase), saponified moringa oil (surfactant) and n-butanol (cotensoative) and a Cotensoative/Surfactant ratio equal to 1 were used. After the preparation of the microemulsioned system, additives were used to prepare drilling fluid: Xanthan Gum (viscosifier) and Baritin (thickening agent). In order the characterization of the fluid, rheological studies were carried out to determine parameters such as the flow limit, behavior index, consistency index and the degree of thixotropy, by varying the viscosifier concentration by 4%, 6% and 8%. The results obtained showed that the fluids showed pseudoplastic behavior, following the Herschell-Bulkley model and according to other studies involving microemulsioned fluids. In addition, with the increase in the percentage of viscosifier, improvements were observed in the properties of the fluid, such as flow limit and thixotropic degree.